The Effect of Government Internal Control System on Regional Financial Accountability - Utami, Fiesty; Ganika, Gerry (Economic Education Analysis Journal, 2021)
The aims of this research is to examines the effect of government internal control system on regional financial accountability partially and simultaneously and using West Java Province as a case study. A quantitative approach utilized in this research. The population is all financial division employees in all 47 OPD in West Java Province. The data collected from 85 respondents as the sample by giving them a questionnaire instrument. This research uses SPSS 20 software to do path analysis in analyzing data. Monitoring (X5), Communication and Information (X4), Control Activities (X3), Risk Asssessment (X2), and Control Environment (X1) are the independent variables, whereas financial accountability (Y) is the dependent variable. The result indicates that the government internal control system affects 53.5% simultaneously positive and siginificant on financial accountability. That means a rising government internal control system would rising regional financial accountability. Partially, control and monitoring acttivities significantly positive in affecting financial accountability. However, control environment, risk assessment, communication and information partially does not significantly impact financial accountability in West Java Province. This paper would be great if the researchers add intervening variables like financial statement or some more dependent variables, which can be used for the future research.